Application Of Client Centered Techniques To Prisoners Of Drug Abuse - Rahmad; Karneli, Yeni (Yana Research, 2024)
This research examines the application of the client-centered approach in counseling drug abuse at the Class IIA Pekanbaru Penitentiary. This technique empowers clients to discover their own solutions through methods such as listening, active engagement, reflecting on feelings, and clarification. The study employs a qualitative descriptive approach to provide an in-depth understanding of the social dynamics surrounding drug abuse.Data was gathered through interviews with three inmates involved in narcotics cases, aged 5 to 8 years. The findings indicate that the client-centered technique is effective, offering personalized attention that meets individual needs and enhancing the likelihood of successful rehabilitation. Moreover, this approach helps inmates gain insight into the causes of their drug abuse and develop strategies to prevent future relapse.